2021
DOI: 10.18844/gjbem.v11i3.5369
|View full text |Cite
|
Sign up to set email alerts
|

Financial technologies’ evolution and traditional banking: A study of retail payments in Nigeria

Abstract: The world of digitalisation is impacting on all aspects of socioeconomic life. This notable change also applies to the financial sector of the global economy. The activities and services of financial technology (FINTECH) overlap with that of traditional banking services. The study seeks to investigate the impact of FINTECH evolution on traditional banking institutions to picture the future of payment systems in Nigeria. Two methods of data analysis were used in the study. An econometric method of data analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…These studies concluded that FI has a positive effect on economic growth, but they did not considthe contribution of education and employment as support tools for promoting the inclusiveness of financial services and products. In contrast, Iriobe et al (2021) had to use a four-year period of quarterly observations due to the scarcity of data on the inclusiveness of financial services and products in developing nations. Another reason is that researchers attempting to measure the inclusiveness of financial services and products using the same parameters for both developed and developing nations without con-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies concluded that FI has a positive effect on economic growth, but they did not considthe contribution of education and employment as support tools for promoting the inclusiveness of financial services and products. In contrast, Iriobe et al (2021) had to use a four-year period of quarterly observations due to the scarcity of data on the inclusiveness of financial services and products in developing nations. Another reason is that researchers attempting to measure the inclusiveness of financial services and products using the same parameters for both developed and developing nations without con-…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to further investigate the impact of illiteracy and unemployment on FI under varied economic conditions as opined byPal et al (2022). Nevertheless, owing to the low educational level in rural areas, point-of-sale (POS) and automated teller machines (ATM) are required to boost the inclusiveness of financial services and products and reduce poverty Iriobe et al (2021). identified these tools as financial technologies that boost the inclusiveness of financial services and products and reduce poverty Onaolapo (2015).…”
mentioning
confidence: 99%
“…However, the study finds its roots in Maslow's and Hertzberg's basic assumption theory of what motivates growth, i.e., what satisfies now and what later comes to satisfies. In other words, unsatisfied needs are basics (foundational) and, when left unsatisfied, distort the fundamentals (signs/indicators) because financial provisions are wrongly allocated-a typical scenario for most African countries [16,17,43,44]. On the one hand, the concept is viewed simply as innovation or re-innovation of financial products and associated accessories, i.e., technology [40][41][42].…”
Section: The Concept Of Financial Engineering (Fe)mentioning
confidence: 99%
“…There are existing studies on financial literacy skills and knowledge in Nigeria ranging from the financial institutions to other establishments. For instance, [7] examined financial literacy and access with implication for women entrepreneurs; [8] analyse financial literacy and financial inclusion for the development of entrepreneurship in Nigeria; [9] interrogated the nexus between financial literacy and business performance of entrepreneurs. From the other context, [10,11] dissect the importance of financial literacy for organizational development and performance.…”
Section: Introductionmentioning
confidence: 99%